2022
DOI: 10.31222/osf.io/w5szk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The APC-Effect: Stratification in Open Access Publishing

Abstract: Current implementations of Open Access (OA) publishing frequently involve Article Publishing Charges (APCs). Increasing evidence emerges that APCs impede researchers with fewer resources in publishing their research OA. We analysed 1.5 million scientific articles from journals listed in the Directory of Open Access Journals to assess average APCs and their determinants for a comprehensive set of journal publications, across scientific disciplines, world regions and through time. Levels of APCs were strongly st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Therefore, the literature suggests that well-resourced actors are better equipped to implement and better able to benefit from the implementation of Open Research practices. of a journal's APC tends to correlate with its prestige [32,33], and that OA publishing may give authors a citation advantage [34,35], the APC model appears to create inequity in the OA publishing space, with well-resourced researchers potentially at an advantage relative to those who are under-resourced [8,32,33,[36][37][38][39][40][41][42][43][44]. In particular, research has shown that women [45], scholars within the social sciences and humanities [46], those from middle-and lower-income nations [47,48] and early career researchers [49] experience disadvantage relative to others when it comes to OA publishing.…”
Section: The Resource-intensive Nature Of Open Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the literature suggests that well-resourced actors are better equipped to implement and better able to benefit from the implementation of Open Research practices. of a journal's APC tends to correlate with its prestige [32,33], and that OA publishing may give authors a citation advantage [34,35], the APC model appears to create inequity in the OA publishing space, with well-resourced researchers potentially at an advantage relative to those who are under-resourced [8,32,33,[36][37][38][39][40][41][42][43][44]. In particular, research has shown that women [45], scholars within the social sciences and humanities [46], those from middle-and lower-income nations [47,48] and early career researchers [49] experience disadvantage relative to others when it comes to OA publishing.…”
Section: The Resource-intensive Nature Of Open Researchmentioning
confidence: 99%
“…3 In a world in which all researchers were equally supported by equally resourced institutions and funding, this would be an even and equitable playing field. However, given that resource stratification of research institutions exists, that research funding is limited, that the size of a journal's APC tends to correlate with its prestige [ 32 , 33 ], and that OA publishing may give authors a citation advantage [ 34 , 35 ], the APC model appears to create inequity in the OA publishing space, with well-resourced researchers potentially at an advantage relative to those who are under-resourced [ 8 , 32 , 33 , 36 44 ]. In particular, research has shown that women [ 45 ], scholars within the social sciences and humanities [ 46 ], those from middle- and lower-income nations [ 47 , 48 ] and early career researchers [ 49 ] experience disadvantage relative to others when it comes to OA publishing.…”
Section: Barriers To the Equitable Implementation Of Open Researchmentioning
confidence: 99%
“…20 In addition, there is a clear Matthew effect (which states "the rich get richer, and the poor get poorer") in terms of differential SDG accomplishment, with lower-income countries clearly making slower progress toward meeting the sustainable development goals agenda. 24 Therefore, uneven SDG progress perpetuates growth differences between and within countries.…”
Section: Efficiency In Achieving the Sdgs Hindered By Inequalities An...mentioning
confidence: 99%
“…Overall, in developing countries the changing climate and inadequate access basic needs pose significant challenges, while in developed countries, responsible demand, and consumption, coupled with ecosystem integrity, pose significant challenges 20 . In addition, there is a clear Matthew effect (which states “the rich get richer, and the poor get poorer”) in terms of differential SDG accomplishment, with lower‐income countries clearly making slower progress toward meeting the sustainable development goals agenda 24 . Therefore, uneven SDG progress perpetuates growth differences between and within countries.…”
Section: Challenges To Sdg Advancement Prior To Covid‐19mentioning
confidence: 99%
“…), has now demonstrated that inequalities manifest within OA publishing due to the 'APC-Effect' (Klebel and 2020;Boudry et al 2019;Siler et al 2018;Batterbury 2017;Gray 2020;Ellers, Crowther, and Harvey 2017;Tennant and Lomax 2019;Monge-Nájera and Monge-Nájera 2018). In addition, institutions with more resources are able to pay higher APCs for their authors (controlling for region and discipline), which not only allows for APC-OA publishing, but doing so in higher prestige, higher cost journals (Klebel and Ross-Hellauer 2022). If OA outputs are looked to as a source of information for evidencebased policy-making, then these findings suggest that the population of researchers who are able to wield influence at the science-policy interface will remain narrow, exclusive, and largely based on privilege.…”
Section: Introductionmentioning
confidence: 99%